Study of Utilization Pattern of Blood And Blood Components in Obstetrics at A Tertiary Care Hospital - Rathod, Pallavi Anil; Jadhao, Avinash Namdeo; Barapatre, Amit Ramesh (Journal of Maternal and Child Health, 2022)
Background: Blood transfusion is a life-saving procedure, but inappropriate use of blood and its components in obstetric emergencies, especially in cases of massive bleeding, increases the risk of morbidity and mortality. The aim of this study was to describe the determinants of blood and blood components in obstetrics in a tertiary care hospital with indications for transfusion for different components during the study. Subjects and Method: A Prospective Observational study was carried from May 2018 to December 2019 at Department of Obstetrics and Gynaecolog,T.N.M.C & B.Y.L.Nair Hospital Mumbai. The independent variables are sociodemographic characteristics, parity, mode of delivery, education, hospital level, while dependent variables are frequency of obstetric transfusion. Frequency of transfusion of blood and its components obtained from case file of patient. The other data were collected by questionnaire. Analysis of 366 Obstetric patients requiring blood transfusion in eighteen months period was done. Qualitative data were presented as frequency and percentages and analysed using the chi-square test. Results: During the whole study 366 of obstetric admission required transfusion of blood and its components. Severe anaemia during pregnancy/postpartum anaemia (51%) were the most common indications for blood product transfusions followed by Accidental Haemorrhage (30%), Caesarean section (10.38%) Genital tract trauma including uterine rupture (11%), Postpartum Haemorrhage’s (13%), Placenta previa (6.5%), Ectopic pregnancies (3.5%), Vesicular mole (3.27%), Retained placenta (3.27%) Ruptured uterus (1%), and Abortion (2.7%). Packed cells (47%) were the most common type of blood and blood products transfused followed by Fresh Frozen Plasma (41.86%). Conclusion: : In obstetric emergencies, correct diagnosis and management of emergencies, A pre- planned, multidisciplinary protocol yields excellent effects in the management. Keywords: blood transfusion, pregnancy, anaemia, obstetric emergencies Correspondence: Avinash N. Jadhao. Associate Professor, Department of Biochemistry Seth GSMC & KEMH Parel Mumbai 400012, India. Email: avinashjadhao@kem.edu. Phone no.91 7718971066.